A (Oxford University Press, 2008)
With a focus throughout on assessment instruments that are feasible, psychometrically sound, and useful for typical clinical requirements, a rating system has been designed to provide evaluations of a measure's norms, reliability, validity, and clinical utility. Standardized tables summarize this information in each chapter, providing essential information on the most scientifically